Meningkatkan Pengetahuan Anak Mengenai Bullying Melalui Metode Show and Tell - Juan Frido Manihuruk; Malida Putri (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2023)
Lately, news of bullying cases in Indonesia has returned to the surface. Reporting on bullying cases at a Solaya Medan orphanage is one of the focuses of discussion in this journal. As a chain that never breaks, bullying continues to color the world of education in Indonesia without serious eradication. Actually bullying is not only in the world of education, but also in the family, performance etc. Especially in the world of street children, street children are often bullied by thugs who are older than them and bigger than them. This all seems to make us realize how serious the problem of bullying is which has become global and serious. Early prevention through moral education, implementation of living with family and responsibility, as well as legal arrangements as an effective start to reduce acts of bullying in society. Settlement through legal channels is of course the last step that requires collaboration and is carried out continuously by all parties without exception, starting from oneself, family, community and the State.